Studying and Modeling the Effect of Graphite Powder Mixing Electrical Discharge Machining on the Main Process Characteristics - Al-Khazraji, Ahmed N.; Amin, Samir A.; Ali, Saad M. (Al-Khwarizmi Engineering Journal, 2015)
Abstract This paper concerned with study the effect of a graphite micro powder mixed in the kerosene dielectric fluid during powder mixing electric discharge machining (PMEDM) of high carbon high chromium AISI D2 steel. The type of electrode (copper and graphite), the pulse current and the pulse-on time and mixing powder in kerosene dielectric fluid are taken as the process main input parameters. The material removal rate MRR, the tool wear ratio TWR and the work piece surface roughness (SR) are taken as output parameters to measure the process performance. The experiments are planned using response surface methodology (RSM) design procedure. Empirical models are developed for MRR, TWR and SR, using the analysis of variance (ANOVA).The best results for the productivity of the process (MRR) obtained when using the graphite electrodes, the pulse current (22 A), the pulse on duration (120 µs) and using the graphite powder mixing in kerosene dielectric reaches (82.84mm³/min). The result gives an improvement in material removal rate of (274%) with respect to the corresponding value obtained when copper electrodes with kerosene dielectric alone. The best results for the tool wear ratio (TWR) of the process obtained when using the copper electrodes, the pulse current (8 A), the pulse on duration (120 µs) and using the kerosene dielectric alone reaches (0.31 %). The use of graphite electrodes, the kerosene dielectric with 5g/l graphite powder mixing, the pulse current (8 A), the pulse on duration (40 µs) give the best surface roughness of a value (2.77 µm).This result yields an improvement in SR by (141%) with respect to the corresponding value obtained when using copper electrodes and the kerosene dielectric alone with the same other parameters and machining conditions. Keywords: EDM, RSM, MRR, TWR, SR, AISI D2die steel, graphite powder mixing.